Application and influence of children’s painting psychotherapy on early childhood education - Zhou, Meng (Transactions on Economics, Business and Management Research, 2024)
This paper deeply discusses the application and far-reaching influence of children’s painting psychotherapy in preschool education. Through combing relevant theories, analyzing practical cases and studying the characteristics of children’s psychological development, this paper reveals that children’s painting psychotherapy, as a non-verbal communication and treatment method, has unique value in helping children express their emotions, solving psychological conflicts and promoting cognitive and social emotional development. Early childhood is a critical period of individual psychological development, and the experience of this stage has a far-reaching impact on his mental health and development throughout his life. However, due to the limited language expression ability of children, traditional psychotherapy methods are often difficult to achieve ideal results in children. As an innovative therapy, children’s painting psychotherapy provides new ways and possibilities for children’s mental health education. The purpose of this paper is to explore the application and effect of children’s painting psychotherapy in early childhood education, analyze its positive influence on children’s psychological development, and provide theoretical support and practical guidance for early childhood educators.